The genome of Mycobacterium africanum West African 2 reveals a lineage-specific locus and genome erosion common to the M. tuberculosis complex. - Stephen D Bentley; Iñaki Comas; Josephine M Bryant; Danielle Walker; Noel H Smith; Simon R Harris; Scott Thurston; Sebastien Gagneux; Jonathan Wood; Martin Antonio; Michael A Quail; Florian Gehre; et al. (PLoS Neglected Tropical Diseases)
Background M. africanum West African 2 constitutes an ancient lineage of the M. tuberculosis complex that commonly causes human tuberculosis in West Africa and has an attenuated phenotype relative to M. tuberculosis. Methodology/principal findings In search of candidate genes underlying these differences, the genome of M. africanum West African 2 was sequenced using classical capillary sequencing techniques. Our findings reveal a unique sequence, RD900, that was independently lost during the evolution of two important lineages within the complex: the "modern" M. tuberculosis group and the lineage leading to M. bovis. Closely related to M. bovis and other animal strains within the M. tuberculosis complex, M. africanum West African 2 shares an abundance of pseudogenes with M. bovis but also with M. africanum West African clade 1. Comparison with other strains of the M. tuberculosis complex revealed pseudogenes events in all the known lineages pointing toward ongoing genome erosion likely due to increased genetic drift and relaxed selection linked to serial transmission-bottlenecks and an intracellular lifestyle. Conclusions/significance The genomic differences identified between M. africanum West African 2 and the other strains of the Mycobacterium tuberculosis complex may explain its attenuated phenotype, and pave the way for targeted experiments to elucidate the phenotypic characteristic of M. africanum. Moreover, availability of the whole genome data allows for verification of conservation of targets used for the next generation of diagnostics and vaccines, in order to ensure similar efficacy in West Africa.